Low-cost automated blood pressure monitors for the detection of pre-eclampsia in rural Tanzanian health clinics: 3 year follow up. (18th April 2012) - Hezelgrave, NL; Unwin, C; Baker, EC; Edmunds, S; Shennan, A
Abstract : Introduction: Regular blood pressure (BP) monitoring is a cost-effective means of early identification and management of hypertensive disease in pregnancy. Yet in much of rural sub-Saharan Africa, the ability to measure BP is hindered by poorly functioning/inadequate or absent equipment, poor staff knowledge and low antenatal care attendance. In Tanzania only 2/3 of women are reported to have their BP measured in pregnancy and the results are frequently inaccurate1. The introduction of a cheap, automated BP monitor suitable for use in low resource settings into rural clinics has the potential to increase detection of pre-eclampsia and reduce perinatal and maternal mortality. Method: 20 validated automated BP devices were distributed to 10 rural clinics in July 2008 together with training about their use. Quantitative and qualitative follow-up was conducted at 36 months. Results: At 36 months, tally of use was 12-21 times/month (median 19). 4/20 devices had broken (one cuff leak, 3 leakage of locally bought batteries) and 2 required new batteries). All devices were reported as useful for antenatal care, with good perceived reliability. Discussion: That all 10 clinics were still using a functional machine 3 years after their introduction is evidence of their acceptability. Batteries have been replaced from staff own wages, a sign of dedication to offering effective care and trust in the device. Concerns remain regarding the long term maintenance of devices; development of machines using solar power, wind-up chargers or sealed lithium batteries is a priority. Their impact of referrals for pre-eclampsia and effect on fetal and maternal morbidity and mortality must be assessed.